2017
DOI: 10.1021/acsami.7b17173
|View full text |Cite
|
Sign up to set email alerts
|

Layered Double Hydroxide and Polypeptide Thermogel Nanocomposite System for Chondrogenic Differentiation of Stem Cells

Abstract: Stem cell therapy for damaged cartilage suffers from low rates of retention, survival, and differentiation into chondrocytes at the target site. To solve these problems, here we propose a two-dimensional/three-dimensional (2D/3D) nanocomposite system. As a new two-dimensional (2D) material, hexagonal layered double hydroxides (LDHs) with a uniform lateral length of 2-3 μm were prepared by a hydrothermal process. Then, tonsil-derived mesenchymal stem cells (TMSCs), arginylglycylaspartic acid-coated LDHs, and ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 43 publications
(83 reference statements)
0
52
0
Order By: Relevance
“…Although the interaction of cells with biomaterials is a crucial step to the success of bioengineering protocol, little advance was made reporting the molecular panorama supporting cell adaptation to biomaterials. On this sense, Lee et al have elegantly proposed an LDH‐based nanocomposite as a new platform material carrying and delivering injectable stem cell in therapy, mainly because these cells exhibit a tendency to adhere onto the nanocomposite and further triggering chondrogenic signaling …”
Section: Resultsmentioning
confidence: 99%
“…Although the interaction of cells with biomaterials is a crucial step to the success of bioengineering protocol, little advance was made reporting the molecular panorama supporting cell adaptation to biomaterials. On this sense, Lee et al have elegantly proposed an LDH‐based nanocomposite as a new platform material carrying and delivering injectable stem cell in therapy, mainly because these cells exhibit a tendency to adhere onto the nanocomposite and further triggering chondrogenic signaling …”
Section: Resultsmentioning
confidence: 99%
“…In their experiments, they prepared Poly(3-Hydroxybutyric acid)-Poly (N-vinylpyrrolidone) fibers loaded with MgAl LDHs and coated over the hydroxyapatite pellets for the realization of bone grafts; the resulting systems showed good compatibility towards MG63 human osteosarcoma 3AB-OS cancer stem cell lines. LDH nanocomposites with arginylglycylaspartic acid and kartogenin were incorporated into a gel together with tonsil-derived mesenchymal stem cells [214]. Interestingly, the cells were observed to aggregate in the nanocomposite system.…”
Section: Cellular Differentiationmentioning
confidence: 99%
“…Upon culturing TMSCs in chondrogenic media, the expression of the chondrogenic markers aggrecan (AGN) and collagen type II (COL2) as well as the accumulation of sulfated glycosaminoglycan‐rich matrix visualized by Alcian blue staining increased, yet COL2 expression was lower in the chondrogenically differentiated TMSCs compared with those of chondrogenically differentiated BM‐MSCs. Later, other groups tested 2‐dimensional (2D)/3D hybrid systems to enhance the chondrogenic differentiation efficiency of TMSCs . These studies revealed significant increases in the chondrogenic markers COL2 and SOX9, demonstrating the improved biofunctionality of chondrogenically differentiated TMSCs by the 2D/3D hybrid cell culture system.…”
Section: Tonsil‐derived Mscs (Tmscs)mentioning
confidence: 99%